The cytotoxic activity of local Cyperus rotundus phenolic extract on human breast cancer cell lines - Sulaiman A. Abdullah; Safaa A. Lateef; Ahmed Majeed Al-Shammari (Iraqi Journal of Cancer and Medical Genetics, 2019)
Background: Cyperus rotundus L. is a herbal plant used worldwide to treat different diseases in traditional medicine, includingmalignancy.Methods: Purified phenolic compounds of C. rotundus rhizomes had been extracted, and GC-MS analysis of phenolic extract wasperformed and conducted according to the National Institute of Standard and Technology. The cytotoxic activity of C. rotundusphenolic extract investigated on various cell lines of human breast cancer (MCF-7, AMJ13, CAL-51) and normal cell line HBL-100 using MTT assay to evaluate IC50. Acridine orange-propidium iodide (AO-PI) stains have been used to investigated theapoptosis effects.Results: results of GC-MS analysis revealed that the extraction of C. rotundus rhizomes contained six phenolic compounds.C. rotundus phenolic extract displayed a significant cytotoxic efficacy against cancer cells MCF-7, CAL -51, and AMJ-13 with(IC50) of (135.3± 2.887, 218.6± 6.009, and 148.4± 4.619) μg /ml, respectively, but it has a negligible effect on HBL-100 at theseconcentrations with IC50 of 329.6± 5.196 μg/ml.Conclusion: The presence of anticancer activity in Cyperus rotundus phenolic extract suggested a further research in screeningthese phytochemicals and investigating their cytotoxic activity against various types of cancer cell lines.